Monocyte CD40 expression in young healthy female smokers and/or oral contraceptives users without additional risk factors for atherosclerosis. Issue 2 (February 2015) - Parahuleva, Mariana S.; Burgazli, Mehmet; Langanke, Eva; Dörr, Oliver; Parviz, Behnoush; Mericliler, Meric; Parahuleva, Nikoleta; Hölschermann, Hans; Erdogan, Ali
Abstract Objective Atherosclerosis, as an inflammatory disease, is characterized by pathologically altered levels of cytokines. We investigated whether smoking and/or oral contraceptives (OCs) affect the CD40/CD40L plasma levels and expression in young females without other risk factors for atherosclerosis. Patients and Methods A case-control single-center design was used. Expression levels of CD40/CD40L were analyzed in healthy non-pregnant, pre-menopausal, non-smoking women who did not take OCs (n = 49), women who currently smoke and take OCs (n = 40), and women who are only smokers (n = 40) or currently take OCs (n = 42). Results In OC users, there was a significant increase in CD40 mRNA expression in circulating monocytes as compared with smokers and control group. However, there were no significant differences in CD40 mRNA expression in monocytes between smokers and non-smokers. Interestingly, CD40 mRNA expression in women taking OCs and currently smoking was significantly decreased compared to only OC users (p < 0.001). With regard to plasma CD40 levels there were significant differences between OC-users and control group. However, contrary to our expectations, there were no significant differences in expression levels of CD40L between four groups. In vitro experiments demonstrated enhanced CD40 mRNA and surface expression in human monocyte-derived macrophages stimulated with estrogens. Furthermore, nicotine pretreatment led to a suppression of estrogens stimulated CD40 induction. Conclusions In young healthy females without additional risk factors for atherosclerosis, OCs, but not smoking, are associated with dramatic changes in CD40 gene and plasma levels. These findings may be providing an important link between OCs and enhancement of pro-inflammatory and atherothrombotic conditions in healthy women.